Metastatic lesions of the uterus, fallopian tubes and ovaries in undifferentiated pleomorphic sarcoma of the left tibia (clinical case) - O. I. Kit; E. V. Verenikina; A. P. Menshenina; L. Yu. Vladimirova; E. A. Kalabanova; T. O. Lapteva; A. A. Barashev; K. S. Eremin; A. Yu. Ardzha (Южно-Российский онкологический журнал, 2024)
Undifferentiated pleomorphic osteosarcoma belongs to the group of rarely occurring tumors. Despite the treatment, the disease progresses in 30–40 % of patients with osteosarcomas. The main route of metastasis of bone tissue sarcomas is hematogenous, while lymphogenic spread is observed less frequently. As a rule, secondary metastatic changes occur in the lungs. Less often there is a secondary lesion of the bones of the skeleton and brain. Metastatic lesion of uterus, fallopian tubes and ovaries in malignant undifferentiated pleomorphic sarcoma is extremely rare. Therefore, we found it interesting to describe a clinical case of such a rare metastatic lesion. Patient K. underwent amputation of the left limb at the level of the lower third of the femur for undifferentiated pleomorphic sarcoma of the left tibia in 2019, and 4 courses of adjuvant polychemotherapy were performed. In 20 months after completion of complex treatment of the primary tumor, complaints of lower abdominal pain, increased body temperature up to 37.8 °C in the evenings appeared. According to the results of follow-up examination, a voluminous, multinodular, solid mass of merging character was detected in the pelvis, with total dimensions of up to 11 cm, and a cavitary mass of up to 5 cm was detected in the posterior vault. A trepan-biopsy of the mass in the projection of the right ovary was performed. The morphological picture in the volume of trepan biopsy specimens is characteristic of spindle cell sarcoma. Metastasis of undifferentiated pleomorphic bone sarcoma (malignant fibrous histiocytoma) is most likely. Due to metastatic lesions of the uterus, fallopian tubes, ovaries, omentum, mesentery and serous membrane of the colon loops, peritoneum of the bladder, surgical intervention in the volume of removal of the distal part of the sigmoid colon, rectosigmoid, upper ampullary parts of the rectum, uterus with fallopian tubes and ovaries, appendix was performed. Immunohistochemical study of the postoperative material revealed that the immunophenotype of tumor cells confirmed the morphological picture typical for undifferentiated pleomorphic bone sarcoma. The patient was further prescribed antitumor drug therapy. This clinical case demonstrates a rare, atypical metastasis of undifferentiated pleomorphic osteosarcoma, which allows to expand the knowledge about the flow of malignant diseases of this localization.